Динамическое программирование и уравнения в частных производных - Беллман Ричард (Мир, 1974)
Экземпляры: КХ (20120817) / Инвентарный номер: 581921 / Цена: 0.76 / Сис.шифр: 517.2 / Авт.знак: Б 43 / ГРНТИ: 27 / ББК: 22